O.14.1Provider use a participatory style with African Americans during glaucoma visits: Presenter(s): Betsy Sleath, University of North Carolina School of Pharmacy, United States. (April 2023) - Carpenter, Delesha; Garcia, Nacire; Budenz, Donald; Muir, Kelly; Robin, Alan
Abstract : Background: Little is known about the extent to which providers involve patients in glaucoma treatment decisions and use a participatory decision-making style. Our purpose was to examine the impact of a pre-visit video/glaucoma question prompt list intervention on provider use of a participatory style and involving patients more in treatment decisions. Methods: African American patients with glaucoma were enrolled and randomized to the intervention or usual care. Intervention patients watched a video on the importance of asking questions during visits and then checked questions that they wanted to ask their provider on a patient question prompt list. Visits were audio-taped, transcribed, and coded. Patients were interviewed after visits. Multivariable regression was used to analyze the data. Findings: One hundred and eighty-eight African American patients agreed to participate (74%); 92 patients were randomized to the intervention group. Forty-six percent of the sample was female; patient age ranged from 29 to 91 years (mean=67 years). Patients completed 7 to 25 years of education (mean=14 years). Forty-three percent of patients were on glaucoma medications for 5 years or more. Providers gave patients treatment choices during ten visits. Providers were more likely to ask patients in the intervention group about their choices for treatment (8.7% versus 2.1%, p<0.05). Patients in the intervention group were not significantly more likely to rate their providers as using a more participatory style. Female (p =0.02) and less educated (p=0.02) patients were less likely to rate their providers as using a participatory style. Rating a provider as using more of a participatory style was not significantly associated with providers asking patients about their choices for treatment. Discussion: Providers were more likely to ask patients in the intervention group about their choices for treatment. The intervention did not increase patient perceptions of provider use of a participatory style.